Feeding systems influence the rumen resistome in yaks by changing the microbiome - Shuli Yang; Jialuo Chen; Jieyi Zheng; Huaming Mao; Feilong Deng; Dongwang Wu; Jianmin Chai (Frontiers in Microbiology)
The rumen microbiome serves as a reservoir of antibiotic-resistance genes (ARGs) with significant implications for public health. This study aimed to investigate the effects of different feeding systems on the rumen resistome in yaks. Yaks that grazed naturally on pasture were used as controls, while the experimental yaks were housed in a high-density pen environment and fed a specially designed diet to optimally meet their nutritional requirements, with increased interactions with farm workers. Metagenomic analysis was performed to assess changes in the rumen microbiome and resistome. Dietary factors influencing changes in the rumen microbiome and resistome were identified. A greater variety of microbiomes associated with carbohydrate digestion was found in yaks under a house-feeding system, such as Stomatobaculum longum and Succiniclasticum ruminis. Although grazing yaks exhibited various dominant antibiotic resistance genes (ARGs) at the class level, house-fed yaks were mainly enriched with tetracycline-resistant genes. A random forest model identified specific ARG signatures for each group, such as Sent_cmlA and Sliv_cmlR (Phenicol) and vanHD (Glycopeptide) prevalent in grazing yaks, while tet44, tetW, tetW/N/W, and tet40 were abundant in house-fed yaks. ARG interactions varied by feeding system, with signature ARGs in each group showing distinct correlations. Nevertheless, strong correlations among ARGs existed regardless of the treatments, such as the positive correlation between tetW and tetW/N/W in both groups. The rumen microbiome was strongly associated with the resistome, especially regarding abundant microbiomes and ARGs. Proteobacteria carrying ARGs were observed in grazing yaks, while Firmicutes served as hosts for ARGs in yaks under a housed feeding system. The specific bacteria contributing to the distinct ARGs in each group were identified. For instance, members of Firmicutes (Clostridium tepidiprofundi) carried their ARG signatures, such as tet44. These findings emphasized that diet, along with environmental factors and farmworker interactions, contributed to changes in the rumen resistome of yaks. This study is the first to discuss how multiple factors within a feeding regime influence the gut resistome, highlighting the drawbacks of intensive feedings with respect to the gut resistome.